2020
DOI: 10.1111/nph.16430
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in plant–microbe interactions over community succession and their effects on plant resistance to herbivores

Abstract: Soil microorganisms can influence the development of complex plant phenotypes, including resistance to herbivores. This microbiome-mediated plasticity may be particularly important for plant species that persist in environments with drastically changing herbivore pressure, for example over community succession.We established a 15-yr gradient of old-field succession to examine the herbivore resistance and rhizosphere microbial communities of Solidago altissima plants in a large-scale field experiment. To assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 68 publications
(85 reference statements)
2
44
0
Order By: Relevance
“…In addition to the plant community, the associated soil microbial community that shifts in a successional community (Hannula et al 2017) can mediate differences in resistance. In a soil microbial transplant experiment, Howard et al (2020) demonstrated that in a common garden, genotypes planted in soil inoculated with the late‐succession soil microbial community were less attractive to T. virgata adults. The combination of soil microbial effects and changes in population genetic composition may synergistically render the plant population unattractive to the insect herbivores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the plant community, the associated soil microbial community that shifts in a successional community (Hannula et al 2017) can mediate differences in resistance. In a soil microbial transplant experiment, Howard et al (2020) demonstrated that in a common garden, genotypes planted in soil inoculated with the late‐succession soil microbial community were less attractive to T. virgata adults. The combination of soil microbial effects and changes in population genetic composition may synergistically render the plant population unattractive to the insect herbivores.…”
Section: Discussionmentioning
confidence: 99%
“…Solidago altissima becomes abundant by Year 3 and remains equally abundant in the older populations (Howard et al 2018). The soil conditions change with succession but all plots follow a common trajectory of increasing soil quality over time (Howard et al 2020).…”
Section: Methodsmentioning
confidence: 99%
“…We previously found that the rhizosphere microbial communities of a native plant, tall goldenrod, Solidago altissima (Asteraceae), shift over oldfield succession in fallow maize fields, with functional effects on their resistance to herbivores. When we inoculated S. altissima with soil microbiomes from a plant community that had been left fallow for 15 years, these plants were more resistant to the specialist goldenrod leaf beetle, Trirhabda virgata , than their counterparts inoculated with early succession microbiomes, paralleling the pattern of greater herbivore resistance observed among goldenrods in late succession communities ( Howard et al., 2020 ). However, it is not known whether this microbiome-mediated resistance associated with the later oldfield succession soils is specific to the community-dominating goldenrods or could more broadly enhance the insect resistance of other plant species as well.…”
Section: Introductionmentioning
confidence: 86%
“…For example, the abundance of pathogenic fungi has been found to decrease over successional time in abandoned agricultural fields ( Hannula et al., 2017 ), suggesting that these shifts are functional and may benefit plants over succession. Our recent work also suggests that these successional shifts in microbial communities may improve plants’ resistance to herbivores ( Howard et al., 2020 ).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation